Textile anti-sea wind corrosion finishing agent and application thereof

By using polyurea compounds produced by chitosan and 1,4-diisocyanate butane, combined with other additives, an anti-sea wind corrosion finishing agent is formed, which solves the corrosion problem of textiles under sea wind, achieves efficient protection effect, and reduces the Textile replacement frequency and improves safety.

CN119265942APending Publication Date: 2025-01-07SUZHOU TANGHUA NANO TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411529035.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing technology lacks specialized textile anti-sea wind corrosion agents, which leads to the susceptibility of textiles sailing at sea, increasing the frequency of replacement and potential safety risks, especially the corrosion of sailboats and sails may lead to safety accidents.

Method used

The polyurea compound produced by reacting chitosan and 1,4-diisocyanate butane through an organotin catalyst at 50-60°C, combined with crosslinking agent, emulsifier, penetrating agent, defoaming agent and water to form an anti-anti- Sea wind corrosion finishing agent and protect textiles through dipping treatment.

Benefits of technology

A protective coating that is wear-resistant, corrosion-resistant and water-resistant has been formed, which has significantly improved the resistance of textiles to sea breeze corrosion, reduced the frequency of textile replacement, and made progress in green chemistry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a textile anti-sea wind corrosion finishing agent and a preparation method and application thereof, the textile anti-sea wind corrosion finishing agent comprises a polyurea compound, and the polyurea compound is formed by polymerizing and grafting chitosan and 1, 4-diisocyanate butane. According to the invention, the isocyanate group of 1, 4-diisocyanate butane and the amino group of chitosan are subjected to polymerization reaction to generate a polyurea compound, the polyurea compound has the characteristics of corrosion resistance, water resistance and wear resistance, and the chitosan has rich hydroxyl groups and can react with carboxyl groups on polyester to form a stable bonding effect, so that a protective coating is formed on the surface of the fiber; and a good anti-corrosion effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of textile post-finishing, and particularly relates to a textile anti-sea breeze corrosion finishing agent and application thereof. Background Art

[0002] From civilian ships and sailboats to military warships, countless textiles are needed. However, when sailing on the sea every day and exposed to sea breeze, these textiles are particularly susceptible to corrosion by sea breeze.

[0003] The corrosiveness of sea breeze mainly comes from its high humidity and salt content. The reason why sea breeze is highly corrosive is mainly because the wind blowing from the sea surface to the ground carries more moisture and has a higher humidity. This high humidity environment provides the necessary conditions for corrosion reactions. The moisture in the sea breeze can undergo oxidation or reduction reactions with the molecular groups in the textiles, resulting in a greater degree of corrosion than other winds. In addition, the temperature difference of the sea surface is small, especially in summer, when the sea surface temperature is low, forming a wind blowing towards the land. At this time, the sea breeze has a stronger wind force and a stronger force, further exacerbating the corrosion effect. The salt in the sea breeze is also an important factor in its strong corrosiveness. The high humidity and high salinity characteristics of the marine atmosphere make it easy for water vapor in the marine atmosphere to adhere to the surface of objects to form a layer of water film. The water film contains dissolved oxygen, chloride ions, sulfate ions and some other salts, forming a highly conductive electrolyte solution. This electrolyte solution environment promotes the rapid corrosion of various objects in contact with sea breeze. The penetration of chloride ions can accelerate local corrosion such as pitting, stress corrosion, intergranular corrosion and crevice corrosion of the objects they contact, making it difficult for various materials on the surface of ships sailing on the sea to form a long-term stable and dense rust layer, resulting in an increase in the corrosion rate. In summary, the corrosiveness of sea breeze is mainly due to its high humidity and salt content. These factors work together to cause sea breeze to cause greater corrosion damage to buildings, metal objects, wood products, textiles, etc.

[0004] At present, there are already market supplies of anticorrosive products for metal products, wood products, electronic products, concrete walls, etc., but there is no special product supply for anticorrosive products for textiles, especially for textiles needed for maritime navigation. There is no corresponding supply of anticorrosive products for textiles. Generally, new products are selected after the products are corroded. For the contemporary era that advocates environmental protection, thrift, and sustainability, if the anticorrosion ability of textiles used for maritime ships can be better improved, the frequency of textile replacement can be reduced. If only decorative textiles are corroded, there is only a problem of replacement waste. If the sails of sailboats are not detected in time after corrosion occurs, safety accidents may occur. Although the use of waterproofing agents and mildew inhibitors can also provide certain protection for textiles used for maritime navigation such as ships to a certain extent, the highly penetrating chloride ions contained in seawater and sea fog can easily destroy these protective layers and damage textiles. Therefore, there is an urgent need to develop anticorrosive agents for textiles that resist seawater and sea breeze corrosion. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a textile anti-sea breeze corrosion finishing agent, wherein the textiles finished with the finishing agent have excellent anti-sea breeze corrosion effect.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0007] A first aspect of the present invention provides a textile anti-sea breeze corrosion finishing agent, which comprises a polyurea compound, wherein the polyurea compound is formed by grafting chitosan with 1,4-diisocyanate butane.

[0008] According to some specific embodiments, the chitosan and the 1,4-diisocyanate butane are reacted at 50-60° C. in the presence of an organic tin catalyst and a solvent to obtain the polyurea compound.

[0009] Furthermore, the organic tin catalyst is dibutyltin dilaurate and / or dioctyltin dilaurate.

[0010] Furthermore, the solvent is methanol.

[0011] Furthermore, the mass ratio of the chitosan, the organotin catalyst, the solvent and the 1,4-diisocyanate butane is 1: 0.2-0.3: 35-45: 0.3-0.5.

[0012] Furthermore, the preparation method of the polyurea compound is specifically as follows: dissolving the chitosan and the organic tin catalyst in methanol, heating to 50-60° C., gradually adding 1,4-diisocyanate butane while stirring, continuing stirring at the reaction temperature after the dropwise addition is completed, maintaining the reaction temperature, and continuing the reaction for 36-48 hours, after the reaction stops, decompressing and filtering, and washing with acetone for 2-3 times after filtering, placing the white powder obtained after washing in a vacuum drying oven, and drying at 80-90° C. for 5-6 hours to obtain the polyurea compound.

[0013] According to some specific embodiments, the textile anti-sea breeze corrosion finishing agent also includes a cross-linking agent, an emulsifier, a penetrant, a defoaming agent and water, wherein the mass ratio of the polyurea compound, the cross-linking agent, the emulsifier, the penetrant, the defoaming agent and the water is 1: 0.05-0.07: 0.1-0.2: 0.07-0.09: 0.05-0.07: 5.0-6.0.

[0014] According to some specific embodiments, the textile anti-sea breeze corrosion finishing agent is prepared by stirring and mixing the polyurea compound, the cross-linking agent, the emulsifier, the penetrant, the defoamer and the water at 50-60°C.

[0015] The second aspect of the present invention provides a textile finishing method, which comprises using the above-mentioned textile anti-sea breeze corrosion finishing agent to perform padding treatment on the textile.

[0016] According to some specific embodiments, the textile is polyester.

[0017] According to some specific embodiments, the textile is a textile for ships.

[0018] According to some specific embodiments, the specific method of the impregnation treatment is: adding the textile anti-sea breeze corrosion finishing agent to the impregnation tank, allowing the textile to pass through the impregnation tank and fully contact with the textile anti-sea breeze corrosion finishing agent, and then pressing the textile with a pressing roller to make the moisture content of the textile 30-40%, and then entering the oven for drying.

[0019] Due to the implementation of the above technical solution, the present invention has the following advantages compared with the prior art:

[0020] The present invention utilizes the isocyanate group of 1,4-diisocyanate butane and the amino polymerization reaction of chitosan to generate a polyurea compound, which has the characteristics of corrosion resistance, waterproofness and wear resistance. Chitosan has abundant hydroxyl groups and can react with the carboxyl groups on polyester to form a stable bonding effect, forming a protective coating on the fiber surface, which produces a good anti-corrosion effect. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with the examples. However, the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to the different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0022] Since the textiles on ships are generally polyester textiles, polyester textiles contain a large number of carboxyl groups, but the carboxyl groups do not have strong reactivity, and it is difficult to achieve functional finishing and processing on them. They can only produce bonding with compounds rich in hydroxyl groups. Therefore, to study polyester preservatives, chemicals rich in hydroxyl groups should be selected as substrates. The present invention produces a compound called polyurea by polymerization reaction of isocyanate and amino compounds, which has the characteristics of corrosion resistance, waterproofness and wear resistance. Chitosan has rich amino groups. After the isocyanate groups in diisocyanate and the amino groups of chitosan are polymerized, a cross-linked compound of a network-like polyurea structure with a nanometer thickness is formed. The compound of this structure can form an anti-corrosion coating on the surface and gaps of the fabric, which can resist the penetration of salt ions, play a role in preventing sea breeze corrosion, and can also improve the wear resistance and tear fastness of the product, forming a good preservative. Chitosan has abundant hydroxyl groups and can react with carboxyl groups on polyester to form stable bonds. In the textile coating process, it is not necessary to add too much cross-linking agent to achieve stable bonding with the coated material. Reducing the use of cross-linking agents can not only maintain the feel and appearance of the textiles, but also reduce production costs, making progress in green chemistry. It can also form a protective coating on the fiber surface, producing a good anti-corrosion effect.

[0023] The technical scheme and technical effects of the present invention are further described below in conjunction with embodiments and comparative examples.

[0024] In the following examples and comparative examples, unless otherwise specified, "%" refers to mass percentage. In the following examples and comparative examples, the raw materials, reagents, etc. used are obtained from the market or prepared by existing methods. For example, the raw materials used in the following examples and comparative examples are from the following sources:

[0025] Chitosan: Water-soluble chitosan with a deacetylation degree of >90% produced by Qingdao Hehai Biotechnology Co., Ltd.

[0026] Dibutyltin dilaurate: CAS No. 77-58-7, chemically pure, Nantong Haotai Chemical Products Co., Ltd.

[0027] 1,4-Diisocyanate butane: CAS No. 4538-37-8, chemically pure, Guangzhou Jiatu Co., Ltd.

[0028] Crosslinking agent: Zhejiang Huasheng Textile Technology Co., Ltd. T-6 crosslinking agent

[0029] Emulsifier: BASF TO-4070

[0030] Penetrant: Rapid penetrant TF-107T from Transfar Intelligent Technology Co., Ltd.

[0031] Defoamer: Foshan Nanhai Datian Chemical Co., Ltd. AT-930 water-based defoamer

[0032] Fabric: Oxford cloth 600d*600d, width 1.52 meters, 230g / ㎡.

[0033] Embodiment 1

[0034] Chitosan and dibutyltin dilaurate were dissolved in methanol in a certain proportion, heated to 50°C, and 1,4-diisocyanate butane was gradually added at a rate of 10 ml / min while stirring. After the addition was completed, stirring was continued at the reaction temperature, and the reaction temperature was maintained for 36 hours. After the reaction stopped, the mixture was filtered under reduced pressure, and washed with acetone twice after filtration. The white powder obtained after washing was placed in a vacuum drying oven and dried at 80°C for 5 hours to obtain a polyurea compound. The mass ratio of chitosan, dibutyltin dilaurate, methanol, and 1,4-diisocyanate butane was: 1:0.2:35:0.3.

[0035] The polyurea compound, the cross-linking agent, the emulsifier, the penetrant, the defoaming agent and water were mixed in a mass ratio of 1:0.05:0.1:0.07:0.05:5.0, heated to 50°C, and stirred for 30 minutes under heat preservation conditions to obtain an anti-sea breeze corrosion finishing agent.

[0036] The anti-sea breeze corrosion finishing agent is added to the dipping and pressing tank. After the fabric has been fully contacted with the anti-sea breeze corrosion finishing agent in the dipping and pressing tank, it is then pressed by a pressing roller. The pressure of the pressing roller is adjusted to make the moisture content of the fabric reach 30%. The fabric then enters the oven and is dried at 180°C to obtain sample 1, and the mildew resistance and corrosion resistance of the sample are tested.

[0037] Embodiment 2

[0038] Chitosan and dibutyltin dilaurate were dissolved in methanol in a certain proportion, heated to 55°C, and 1,4-diisocyanate butane was gradually added at a rate of 12 ml / min while stirring. After the addition was completed, stirring was continued at the reaction temperature, and the reaction temperature was maintained for 42 hours. After the reaction stopped, the mixture was filtered under reduced pressure, and washed with acetone for 3 times. After washing, the white powder obtained was placed in a vacuum drying oven and dried at 85°C for 5.5 hours to obtain a polyurea compound. The mass ratio of chitosan, dibutyltin dilaurate, methanol, and 1,4-diisocyanate butane was: 1:0.25:40:0.4.

[0039] The polyurea compound, the cross-linking agent, the emulsifier, the penetrant, the defoaming agent and water were mixed in a mass ratio of 1:0.06:0.15:0.08:0.06:5.5, heated to 55°C, and stirred for 35 minutes under heat preservation conditions to obtain an anti-sea breeze corrosion finishing agent.

[0040] The anti-sea breeze corrosion finishing agent is added to the dipping and pressing tank. After the fabric has been fully contacted with the anti-sea breeze corrosion finishing agent in the dipping and pressing tank, it is then pressed by a pressing roller. The pressure of the pressing roller is adjusted to make the moisture content of the fabric reach 40%. The fabric then enters the oven and is dried at 185°C to obtain sample 2, and the mildew resistance and corrosion resistance of the sample are tested.

[0041] Embodiment 3

[0042] Chitosan and dibutyltin dilaurate were dissolved in methanol in a certain proportion, heated to 60°C, and 1,4-diisocyanate butane was gradually added at a rate of 12.5 ml / min while stirring. After the addition was completed, stirring was continued at the reaction temperature, and the reaction temperature was maintained for 48 hours. After the reaction stopped, the mixture was filtered under reduced pressure, and washed with acetone for 3 times. After washing, the white powder obtained was placed in a vacuum drying oven and dried at 90°C for 6 hours to obtain a polyurea compound. The mass ratio of chitosan, dibutyltin dilaurate, methanol, and 1,4-diisocyanate butane was: 1:0.3:45:0.5.

[0043] The polyurea compound, the cross-linking agent, the emulsifier, the penetrant, the defoaming agent and water were mixed in a mass ratio of 1:0.07:0.2:0.09:0.07:6.0, heated to 60°C, and stirred for 40 minutes under heat preservation conditions to obtain an anti-sea breeze corrosion finishing agent.

[0044] The anti-sea breeze corrosion finishing agent is added to the dipping and pressing tank. After the fabric has been fully contacted with the anti-sea breeze corrosion finishing agent in the dipping and pressing tank, it is then pressed by a pressing roller. The pressure of the pressing roller is adjusted to make the moisture content of the fabric reach 40%. The fabric then enters the oven and is dried at 190°C to obtain sample 3, and the mildew resistance and corrosion resistance of the sample are tested.

[0045] Embodiment 4

[0046] Chitosan and dioctyltin dilaurate were dissolved in methanol in a certain proportion, heated to 60°C, and 1,4-diisocyanate butane was gradually added at a rate of 12.5 ml / min while stirring. After the addition was completed, stirring was continued at the reaction temperature, and the reaction temperature was maintained for 48 hours. After the reaction stopped, the mixture was filtered under reduced pressure, and washed with acetone for 3 times. After washing, the white powder obtained was placed in a vacuum drying oven and dried at 90°C for 6 hours to obtain a polyurea compound. The mass ratio of chitosan, dibutyltin dilaurate, methanol, and 1,4-diisocyanate butane was: 1:0.3:45:0.5.

[0047] The polyurea compound, the cross-linking agent, the emulsifier, the penetrant, the defoaming agent and water were mixed in a mass ratio of 1:0.07:0.2:0.09:0.07:6.0, heated to 60°C, and stirred for 40 minutes under heat preservation conditions to obtain an anti-sea breeze corrosion finishing agent.

[0048] The anti-sea breeze corrosion finishing agent is added to the dipping and pressing tank. After the fabric has been fully contacted with the anti-sea breeze corrosion finishing agent in the dipping and pressing tank, it is then pressed by a pressing roller. The pressure of the pressing roller is adjusted to make the moisture content of the fabric reach 40%. The fabric then enters the oven and is dried at 190°C to obtain sample 4, and the mildew resistance and corrosion resistance of the sample are tested.

[0049] Comparative Example 1 (Comparison with commercially available waterproofing agent)

[0050] The waterproofing agent, the cross-linking agent, the emulsifier, the penetrant, the defoaming agent and water were mixed in a mass ratio of 1:0.07:0.2:0.09:0.07:6.0, heated to 60°C, and stirred for 40 minutes under heat preservation conditions to obtain a waterproof finishing agent.

[0051] The waterproof finishing agent is added to the dipping tank. After the fabric has been in full contact with the waterproof finishing agent in the dipping tank, it is then pressed by a pressing roller. The pressure of the pressing roller is adjusted to make the moisture content of the fabric reach 40%. The fabric then enters the oven and is dried at 190°C to obtain sample 5, which is then tested for mildew resistance and corrosion resistance.

[0052] The waterproof agent is Teflon three-proof finishing agent CP-SLA

[0053] Comparative Example 2 (Comparison with commercially available mildew inhibitors)

[0054] The mildew-proofing agent, cross-linking agent, emulsifier, penetrant, defoamer and water were mixed in a mass ratio of 1:0.07:0.2:0.09:0.07:6.0, heated to 60°C, and stirred for 40 minutes under heat preservation conditions to obtain a mildew-proof finishing agent.

[0055] The anti-mildew finishing agent is added to the dipping and pressing tank. After the fabric has been fully in contact with the anti-mildew finishing agent in the dipping and pressing tank, it is then pressed by a pressing roller. The pressure of the pressing roller is adjusted to make the moisture content of the fabric reach 40%. The fabric then enters the drying oven and is dried at 190°C to obtain sample 6, which is then tested for mildew resistance and corrosion resistance.

[0056] The mildew-proof agent is ATE9260 from Shanghai Hutt Chemical Co., Ltd.

[0057] Comparative Example 3 (Comparison of a mixed finishing agent of a commercially available waterproofing agent and a mildewproofing agent)

[0058] The waterproofing agent, the mildewproofing agent, the cross-linking agent, the emulsifier, the penetrant, the defoaming agent and water were mixed in a mass ratio of 0.5:0.5:0.07:0.2:0.09:0.07:6.0, heated to 60°C, and stirred for 40 minutes under heat preservation conditions to obtain a mixed finishing agent.

[0059] The mixed finishing agent is added to the dipping and pressing tank. After the fabric has been fully in contact with the mixed finishing agent in the dipping and pressing tank, it is then pressed by a pressing roller. The pressure of the pressing roller is adjusted to make the moisture content of the fabric reach 40%. The fabric then enters the oven and is dried at 190°C to obtain sample 7, which is then tested for mildew resistance and corrosion resistance.

[0060] The waterproof agent is Teflon three-proof finishing agent CP-SLA

[0061] The mildew-proof agent is ATE9260 from Shanghai Hutt Chemical Co., Ltd.

[0062] Test results

[0063] The mildew resistance of textiles is tested in accordance with GB / T 24346-2009 “Evaluation of Mildew Resistance of Textiles”.

[0064] The test method for corrosion resistance is as follows: first test the tear strength of the sample, then soak the sample in 30% sodium chloride solution and 30% hydrochloric acid solution respectively. The fabric needs to be soaked for 72 hours before testing its tear strength.

[0065] The results of the 7 samples are as follows:

[0066]

[0067] As can be seen from the above table, the polyurea compound of the present application has a more excellent anti-mildew effect and anti-corrosion effect compared with the existing three-proof finishing agent, anti-mildew finishing agent or the combination of the three-proof finishing agent and the anti-mildew finishing agent.

[0068] The above detailed description of the present invention is intended to enable persons familiar with the art to understand the contents of the present invention and implement them. It does not limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A textile anti-sea breeze corrosion finishing agent, characterized in that: The invention comprises a polyurea compound, wherein the polyurea compound is formed by grafting chitosan and 1,4-diisocyanate butane through polymerization.

2. The textile anti-sea breeze corrosion finishing agent according to claim 1, characterized in that: The chitosan and the 1,4-diisocyanate butane are reacted at 50-60° C. in the presence of an organic tin catalyst and a solvent to obtain the polyurea compound.

3. The textile anti-sea breeze corrosion finishing agent according to claim 2, characterized in that: The organic tin catalyst is dibutyltin dilaurate and / or dioctyltin dilaurate.

4. The textile anti-sea breeze corrosion finishing agent according to claim 2, characterized in that: The solvent is methanol.

5. The textile anti-sea breeze corrosion finishing agent according to claim 2, characterized in that: The feeding mass ratio of the chitosan, the organic tin catalyst, the solvent and the 1,4-diisocyanate butane is: 1: 0.2-0.3: 35-45: 0.3-0.

5.

6. The textile anti-sea breeze corrosion finishing agent according to claim 1, characterized in that: The textile anti-sea breeze corrosion finishing agent also includes a cross-linking agent, an emulsifier, a penetrant, a defoaming agent and water, wherein the mass ratio of the polyurea compound, the cross-linking agent, the emulsifier, the penetrant, the defoaming agent and the water is 1: 0.05-0.07: 0.1-0.2: 0.07-0.09: 0.05-0.07: 5.0-6.

0.

7. The textile anti-sea breeze corrosion finishing agent according to claim 6, characterized in that: The textile anti-sea breeze corrosion finishing agent is prepared by stirring and mixing the polyurea compound, the cross-linking agent, the emulsifier, the penetrant, the defoamer and the water at 50-60°C.

8. A textile finishing method, characterized in that: The textile is subjected to padding treatment using the textile anti-sea breeze corrosion finishing agent as claimed in any one of claims 1 to 7.

9. The textile finishing method according to claim 8, characterized in that: The textile is polyester.

10. The textile finishing method according to claim 8, characterized in that: The specific method of the padding treatment is: adding the textile anti-sea breeze corrosion finishing agent into the dipping and pressing tank, allowing the textile to pass through the dipping and pressing tank and fully contact with the textile anti-sea breeze corrosion finishing agent, and then rolling the textile with a pressing roller to make the moisture content of the textile 30-40%, and then entering the oven for drying.